Pengaruh Budaya Oranisasi, Human Capital dan Employee Engagement Terhadap Kinerja Pegawai Dinas Peternakan Provinsi Aceh - Fijar Wahyudi (SUMBER INFORMASI MANAJEMEN BISNIS DAN AKUNTANSI, 2024)
This study aims to examine the influence of organizational culture, human capital, and employee engagement on the performance of employees in the Aceh Provincial Livestock Service, both individually (partially) and together (simultaneously). This study uses quantitative methods. The sample in this study is all employees of the Aceh Province Livestock Service. Data collection techniques using questionnaires obtained by distributing questionnaires to employees who work in the Aceh Provincial Livestock Service. The analytical method used is multiple linear regression. The results of this study found that organizational culture, human capital, and employee engagement influence employee performance, both individually (partially) and together (simultaneously).